2004
DOI: 10.1109/lpt.2004.827102
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Two-Photon Absorption Microcavity Autocorrelator

Abstract: Abstract-A GaAs-AlAs microcavity device has been used as a photodetector in an autocorrelator for measuring the temporal pulsewidth of 1.5-m optical pulses. Enhancement of the two-photon absorption photocurrent due to the microcavity structure results in an autocorrelation (average power times peak power) sensitivity of 9 3 10 4 (mW) 2 , which represents two orders of magnitude improvement when compared with conventional autocorrelators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The main difficulty with using TPA for highspeed optical sampling is its inherent inefficiency, which means that such systems either require high optical intensities or very long detectors, making them unsuitable for practical telecommunications applications. One possible way to overcome this efficiency problem is to employ a semiconductor microcavity (Krug et al, 2004), which should significantly enhance the TPA response of the device, and enable the implementation of a practical sampling element for high-speed optical systems.…”
Section: Two Photon Absorption (Tpa) In Semiconductor Devicesmentioning
confidence: 99%
“…The main difficulty with using TPA for highspeed optical sampling is its inherent inefficiency, which means that such systems either require high optical intensities or very long detectors, making them unsuitable for practical telecommunications applications. One possible way to overcome this efficiency problem is to employ a semiconductor microcavity (Krug et al, 2004), which should significantly enhance the TPA response of the device, and enable the implementation of a practical sampling element for high-speed optical systems.…”
Section: Two Photon Absorption (Tpa) In Semiconductor Devicesmentioning
confidence: 99%
“…The front pdoped mirror consists of 9 pairs while the back n-doped mirror consists of 18 pairs designed for reflectivity at 1550nm. The device studied was a 100µm diameter vertical structure [3]. Fig.…”
Section: Principle Of Tpa Sampling Operationmentioning
confidence: 99%
“…Several groups have demonstrated that TPA or 3PA based processes can be effective for pulse diagnostics in the femtosecond and picosecond time range with photodiodes using Si [2,3], GaAsP [2,[4][5][6][7], InGaAs [8], SiC [9,10], ZnSSe [11], GaN [12], light-emitting diodes using AlGaAs [13], laser diodes using GaAsP [3], GaAs/AlGaAs [14], GaN [15] and photocathodes using CsI and CuI PMTs [16] in autocorrelator schemes. Other semiconductor waveguides and microcavity structure devices were also developed [17][18][19]. Semiconductor sensors offer high sensitivity and ease of use in compact integrated solid-state devices which are insensitive to frequency chirp and polarization.…”
Section: Introductionmentioning
confidence: 99%